Speech recognition in flight simulator - Rustamov, S.; Gasimov, E.; Hasanov, R.; Jahangirli, S.; Mustafayev, E.; Usikov, D. (IOP Publishing, 2018)
The article is devoted to the investigation of speech recognition in Flight Simulator cockpit. We have done research and developed software for speech recognition in Flight Simulator with limited vocabulary in C# from scratch. The speech recognition system works in real time and offline mode in Windows platform. We used Mel Frequency Cepstral Coefficients and Linear Predictive Coefficients feature extraction algorithms and trained the system by multilayer artificial neural networks. The User Interface of platform is highly functional and allows users to update system parameters through the interface. Our Speech Recognition system results are compared to the results of Microsoft Speech SDK and received satisfactory achievement.
Keywords: Air traffic control.; Automatic speech recognition.